2004
DOI: 10.1017/s0031182003004232
|View full text |Cite
|
Sign up to set email alerts
|

Ion channels ofFasciola hepaticaincorporated into planar lipid bilayers

Abstract: Ion channels are important target sites of anthelmintics, but little is known about those in Fasciola hepatica. In this work, we applied a planar lipid bilayer technique to characterize the properties of single ion channels in F. hepatica. Under a 200/40 mM KCl gradient, a large conductance channel of 251 pS was observed in 18% of the membranes studied. The channel was selective to K(+) over Cl(-) with a permeability ratio of K(+) to Cl(-) (PK/PCl) of 4.9. Open state probability (Po) of the channel was less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The relative permeability ratio P K /P Cl calculated was about 5, similar to the reported values for potassium channels in Fasciola hepatica [Jang et al, 2004] and Dictyostelium discoideum [Yoshida et al, 1997]. Further work is necessary to obtain a complete biophysical characterization of this channel as well as its possible cellular functions and molecular identity.…”
Section: Discussionsupporting
confidence: 80%
“…The relative permeability ratio P K /P Cl calculated was about 5, similar to the reported values for potassium channels in Fasciola hepatica [Jang et al, 2004] and Dictyostelium discoideum [Yoshida et al, 1997]. Further work is necessary to obtain a complete biophysical characterization of this channel as well as its possible cellular functions and molecular identity.…”
Section: Discussionsupporting
confidence: 80%
“…Characterization of K + channels, although detailed and exhaustive in some cases, is mainly limited to bacterial (KcsA) and mammalian channels, with some particular cases of model organisms like Drosophila and C. elegans . In Fasciola hepatica [60]and Dictyosteliumdiscoideum [61] the presence of K + channels with relative permeability ratio P K /P Cl of 5 and 7, respectively, have been previously reported, suggesting that the selectivity of some channels in these organisms is not as high as for bacterial or mammalian K + channels.…”
Section: Discussionmentioning
confidence: 96%
“…This is, to the best of our knowledge, the first such study on muscle from F. hepatica. It is only the second voltage-clamp study on cells of any type from this organism, a non-specific cation current having recently been described in neurons isolated from F. hepatica (Kim et al 2002), although ion channels from F. hepatica have also been studied in lipid bilayers (Jang et al 2003). We describe here outward K + -currents evoked during depolarization, along with their unusual pharmacological profile.…”
Section: Introductionmentioning
confidence: 94%
“…Another possibility is that an opposing inward current may have shifted the reversal potential positively with regard to E K , with either a chloride (Large & Wang, 1996) or a non-specific cation conductance (Loirand et al 1991) being possible candidates. A non-specific cation current has recently been identified in neurons isolated from F. hepatica (Kim et al 2002), while both K + -and Cl x -channels have been identified in lipid bilayer experiments using extracts from homogenized flukes (Jang et al 2003). Unfortunately, this technique does not allow the tissue of origin to be identified.…”
Section: Electrophysiological Characterization Of the Outward Currentmentioning
confidence: 99%
See 1 more Smart Citation